2014
DOI: 10.1590/2179-8087.040213
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas da madeira de teca termorretificada

Abstract: RESUMOO objetivo deste estudo foi determinar o efeito de tratamentos termorretificadores nas propriedades físicas (densidade e teor de umidade) da madeira de teca (Tectona grandis L. f.), proveniente de plantios de diferentes espaçamentos. Amostras de madeira de cerne e alburno foram termorretificadas a 180°C e 200°C durante 2 horas e 30 minutos. A termorretificação afetou mais a densidade do cerne do que a densidade do alburno. As madeiras de cerne e alburno apresentaram uma redução média de 52% no teor de um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For the same process and temperature, Bellon et al (2014) also reported the same pattern of reduction in the ρ 12 for both eucalyptus and teak, with 10% and 16%, respectively, for TMEW and TMTW. Lower reductions were reported by Lopes et al (2014b) for TMTW sapwood (6%) and heartwood (9%), in a laboratory-scale process at 180 and 200°C. Thermal modification (120°C to 180°C) caused a slight decrease (3.58%) in the density of teak wood (Priadi et al 2019).…”
Section: Physical Propertiesmentioning
confidence: 66%
See 2 more Smart Citations
“…For the same process and temperature, Bellon et al (2014) also reported the same pattern of reduction in the ρ 12 for both eucalyptus and teak, with 10% and 16%, respectively, for TMEW and TMTW. Lower reductions were reported by Lopes et al (2014b) for TMTW sapwood (6%) and heartwood (9%), in a laboratory-scale process at 180 and 200°C. Thermal modification (120°C to 180°C) caused a slight decrease (3.58%) in the density of teak wood (Priadi et al 2019).…”
Section: Physical Propertiesmentioning
confidence: 66%
“…than for TMEW (31% or 3.5 p.p.). Lopes et al (2014b) reported reductions in hygroscopicity varying from 46% to 54%, and 45% to 54%, respectively for TMTW heartwood and sapwood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cademartori et al (2015 also found a decrease in dimensional stability due to thermal modification in Eucalyptus grandis and Eucalyptus saligna woods. Lopes et. al.…”
Section: Resultsmentioning
confidence: 99%